PENGARUH SELF ASSESSMENT SYSTEM BAGI WAJIB PAJAK TERHADAP KEPATUHAN DALAM MEMBAYAR PAJAK DI KOTA SUNGAI PENUH - Wawan Novianto; Firdaus Firdaus; Eka Retno Saputra (Journal of Innovation Research and Knowledge, 2022)
This study aims to determine the effect of the self-assessment system for taxpayers on compliance in paying taxes in full river tax cities. An approach that primaryly uses paradigms in developing science (such as reduction to variables, specific questions, theoretical testing, using measurements and observations, thoughts about causation, and hypotheses) that uses research strategies such as surveys and experiments that use statistical data. The scope in this study is in a full river city and focuses on taxpayers. Based on the results of research and discussion on X1 and Y in Full River City Taxpayers, it can be concluded as follows: The value of R Squre above will be changed in the form of percent to find out how much X1 contributes to Y in Full River City Taxpayers. The R Squre value of 0.33.2 if percented at 33.2% means that the magnitude of the influence of X1 Y is 33.2% while the remaining 66.8%. Influenced by the variables studied in this study.